Analysis of Women's Representation in Parliament in Indonesia Using Robust Regression Estimation-S - Suma, I Gede Dewangga Jati; Harsanti, Titik (UI Scholars Hub, 2024)
Women's representation in parliament is a very important issue to study because one of the SDGs goals is gender equality. Women's representation in parliament in Indonesia is still low, only reaching 21.74 percent in 2022. The low representation of women in parliament will certainly hinder the role of women in leading decision making in political life. Studies regarding women's representation in parliament are generally discussed qualitatively, so this article tries to examine this problem with a quantitative approach. The method used in this research is robust S-estimation regression which can form a better model by minimizing the influence of extreme values. The results of data processing in 509 districts/cities in Indonesia show that women with a high school education or above, women who access the internet and the level of urbanization have a significant effect on women's representation in parliament in Indonesia in 2022, while women's married status does not have a significant effect on women's representation in parliament. in Indonesia in 2022.